Tracing the development & transformation of religious opinions & the fatwa institution in Malaysia - Siti Hadija Mohd (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Malaysia is the only country in the world to have multiple official muftis. In addition to that, Malaysia also puts fatwa and matters related to Islam under state administration rather than under the federal authority. This unique phenomenon has struck a lot of curiosity of its historical roots. Without dismissing the legal perspectives of it but focusing more intensely on the history side of it, this research traces the development of religious opinions and fatwa institution in British Malaya from the commencement of the terms in Pangkor Treaty up until now. The research has asked how had British colonialism in Malaya affected the growth, issuance and development of fatawa and religious matters and how had the measures the British took in Malaya impacted the transformation of the country's state-based fatwa institution. Other than that, the study has inquired the development and transformation of this institution and its related agencies post-independence until the current day. To answer these questions, the study followed through with evidences from many primary and secondary sources, through inductive analysis and thematic study, all of which to serve the historical narration in question. Many primary manuscripts, memos, newspaper articles, reports, minutes of meetings and court cases were analysed inductively to create the narrative sought in the objectives. Several interviews were also conducted with five of the fourteen contemporary Malaysian muftis. The study has, thus, achieved its objective to highlight the tools and strategies used by the British in intervening with Islamic matters. Additionally, the study through its investigations has found repeating themes within many different cases and events in regards to the issuance and application of fatwa. Ultimately, the study has also explored different possibilities, and suggested them as well, in harmonising and standardising the state-based fatwa issuance in Malaysia. Among the suggestions are to have the National Fatwa Council to be neater and more robust in fatwa research because it gives more confidence to the states to receive it without a lot of questions, and where it will help towards aligning fatwa issuance. Therefore, the National Fatwa Council is encouraged to provide more exposure to its officers with training, local or international short-term career placement, conducting more fatwa dialogues and so on. In addition to that, adequate research facilities and funds as well as good relations between researchers will help in producing truly quality research. As a long-term measure, the setting up of a Fatwa Coordination Centre should be sought to make the fatwa institution in Malaysia more aligned and able to address the problem of Muslims more effectively.